Exploring Students' Metacognition in Numeracy Problem Solving: The Role of Reflective and Impulsive Cognitive Styles - Hermin, Arwini Puspita; Pathuddin, Pathuddin; Lefrida, Rita; Alfisyahra, Alfisyahra (Jurnal Pendidikan MIPA, 2025)
The purpose of this study was to describe the metacognition of grade IX students of SMP Negeri 19 Palu in solving numeracy problems based on reflective and impulsive cognitive styles. Metacognition in this study includes three aspects namely awareness, regulation, and evaluation observed at each stage of problem solving according to Polya's model. This descriptive qualitative research used Matching Familiar Figures Test (MFFT-2021), numeracy written test, think-aloud protocol, and in-depth interviews for data collection. In-depth study subjects consisted of two students, one each with reflective cognitive style and one with impulsive cognitive style. The results showed that at the stage of understanding the problem, reflective students showed high awareness and were able to organize their thoughts to understand the context of the problem in depth, while impulsive students tended to be faster in understanding the problem without in-depth analysis. At the stage of developing a plan, reflective students perform good regulation and evaluate the plan made, while impulsive students show awareness and regulation, but the evaluation of the plan is not always consistent. At the stage of implementing the plan, reflective students are able to evaluate the ongoing process, although this evaluation is more visible at the final stage, while impulsive students are less consistent in evaluation during the implementation of the plan, with evaluation only appearing at the final stage. Finally, at the looking back stage, reflective students showed a clear evaluation, although awareness and regulation were not significantly visible, while impulsive students only showed evaluation at the final stage without any deep reflection on the process that had been passed. Overall, reflective cognitive style tends to produce a more complete and in-depth metacognitive involvement in each stage of problem solving, while impulsive style shows a more limited and less consistent involvement in the evaluation aspect.      Keywords: metacognition, numeracy, cognitive style, reflective, impulsive.